Vaquero Country: Tracing the Latin Origins of the American Cowboy - David Cota (The Toro Historical Review, 2025)
This research paper explores the historical origins of the quintessential American cowboy. The paper examines how vaqueros of indigenous and Latino descent greatly influenced cowboys. We used how practices such as roping cows, hunting for wildlife, and cowpunching are all practices that are still prominent in modern times. This paper shows the reason why proper representation is important in all forms of media.